2017
DOI: 10.1111/acps.12836
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive–behavioural therapy for adult attention‐deficit hyperactivity disorder: a proof of concept randomised controlled trial

Abstract: This is the first randomised controlled trial to provide preliminary evidence of efficacy and acceptability of individual formulation-based CBT for ADHD when added to TAU over TAU alone. This approach now needs to be tested in a larger multicentred randomised controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Results of the risk of bias assessment are presented in Table 1. Only one of the included records was assessed as having a low risk of bias across all five domains and that was for only one of the interventions within the trial (Schonenberg et al, 2017), and nine records were assessed as having a low risk of bias in four out of five domains (Dittner, Hodsoll, Rimes, Russell, & Chalder, 2018; Gu, Xu, & Zhu, 2018; Janssen et al, 2018; Philipsen et al, 2015; Salomone et al, 2015; Stern, Malik, Pollak, Bonne, & Maeir, 2016; Vidal et al, 2013; Young et al, 2015, 2017). For a significant number of studies, it was not possible to assess the risk of bias in at least one of the five domains due to insufficient information.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Results of the risk of bias assessment are presented in Table 1. Only one of the included records was assessed as having a low risk of bias across all five domains and that was for only one of the interventions within the trial (Schonenberg et al, 2017), and nine records were assessed as having a low risk of bias in four out of five domains (Dittner, Hodsoll, Rimes, Russell, & Chalder, 2018; Gu, Xu, & Zhu, 2018; Janssen et al, 2018; Philipsen et al, 2015; Salomone et al, 2015; Stern, Malik, Pollak, Bonne, & Maeir, 2016; Vidal et al, 2013; Young et al, 2015, 2017). For a significant number of studies, it was not possible to assess the risk of bias in at least one of the five domains due to insufficient information.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies compared CBT with TAU (Dittner et al, 2018; Emilsson et al, 2011; Safren et al, 2005; Young et al, 2015, 2017) CBT produced an improvement in independent and self-reported ADHD symptoms, both for group (Emilsson et al, 2011; Young et al, 2015) and individual (Dittner et al, 2018; Safren et al, 2005) therapy. Improvements included changes in inattentive and hyperactive-impulsive symptoms and were based on measures taken at pre- and post-treatment and at follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations